Transformationen deutscher Polenstereotype in der Prosa von Artur Becker und Maria Kolenda - Piontek, Sławomir (Studia Germanica Posnaniensia, 2017)
The article analyzes the transformations of German stereotypes of Poles in current prose of Polish immigrant authors in Germany. The authors show a particularly keen awareness of the long term stereotypes and try to change their meaning by means of detachment, humor and irony.